Police officers’ and Registered Intermediaries’ use of drawing during investigative interviews with vulnerable witnesses - Mattison, Michelle L. A. (Psychology, crime & law, 2020)
Attempts to enhance episodic retrieval focus largely on verbal strategies which do not always address the limited or impaired free recall ability of vulnerable witnesses. Asking a witness to draw while recalling episodic information has long been deemed an effective method of improving communication and cognitive performance. Thus far, research has revealed these effects within laboratory settings but with scarce attention paid to real-life interview practice. In this paper, we explore police officers’ and Registered Intermediaries’ use of drawing during investigative interviews with vulnerable witnesses. A sample of specialist practitioners (n = 85), comprising of vulnerable witness interviewing police officers (n = 50) and Registered Intermediaries (n = 35) completed a self-report questionnaire. As expected, frequent use of drawing was reported by both practitioner groups, and there was a positive correlation between reported use and perceived effectiveness. There were similarities between groups in reported techniques employed when using drawing, but some differences were apparent and these were attributed to the differing functions in police and Registered Intermediary roles. Overall, a consensus between empirical research and practice is evident, but these findings warrant further exploration in order to establish whether such practice is wide-spread.